Teaching STRATEGies USEd IN E-LEARNING MATERIALs FOR senior high schools - Oxtapianus Tawarik; Ikhsanudin Ikhsanudin; Dwi Riyanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
Researchers have conducted research about the role of technology in teaching and learning process (Arthur, et al. 2008, Erben, et al. 2009, Kali and Linn. 2008, and Yang, 2005). They found that the effectiveness of the students' learning and academic achievement can be greatly increased by the use of technology since technology provides opportunities to make the language learning more enjoyable, productive and effective. E-learning material is one of the technologies that can be used by English teachers to support their teaching instructions. This article is aimed at introducing a strategy for teaching reading through e-learning material and providing theoretical and empirical proofs about the benefits and the problems in e-learning material in reading class. However, in order to get the optimum result of integrating the technology in teaching English as a foreign language, a proper teaching strategy is urgently needed. Thus, this article covers: definition of teaching strategy and e-learning and each component, strategy of e-learning, benefit of e-learning, e-learning program, and distance learning. Through the use of media technology, it is hoped it could improve the quality of teaching and learning processes.